Formation of co-axial jets and their downstream development - Çelik, Nevin; Bettenhausen, Daniel W.; Lovik, Ryan D. (My University, 2012)
A comprehensive numerical simulation has been performed to inter-relate the fluid mechanics of the formation of co-axial jets and their development downstream of the plane of jet emergence. The fluid flow was modeled as being turbulent, with corresponding Reynolds numbers in the jet-formation section of 10000, 20000, and 50000. The model was based on a fully developed pipe flow encountering a double-pipe arrangement and splitting between the two pipes. Subsequent to flow development in the central pipe and in its enveloping annulus, the flow exited into a large free space and became a co-axial free jet. The simulations were performed for geometric parameters which varied the relative cross sections of the central pipe and of the annulus and also varied the length of the jet-formation section. The overall pressure drop responsible for both the jet formation and for the subsequent free-jet development was found to be due to friction in contradistinction to inertial losses. At the jet exit, the velocity profile is discontinuous because of the intrusive presence of the walls of the pipes which bound the jet-formation section. These intrusions cause a double-humped velocity profile which disappeared with decreasing downstream distance from the jet origin. At sufficient downstream distances, the width of the jet was found to be independent of both the geometrical parameters and the Reynolds number. © 2012 TIBTD Printed in Turkey.
Keywords: CFX; Co-axial jet; Jet formation; Jet spreading; Numerical simulation; Turbulent jet flow